Impassioned belief - Ridge, Michael (Oxford : Oxford Scholarship Online, 2014)
We all form judgments about what ways of life are worthwhile, what we are morally required to do and so on. These so-called "normative" judgments have seemed puzzling in part because they exhibit both belief-like and desire-like features. Traditional cognitivist theories hold that these judgments are beliefs rather than desires; traditional non-cognitivist theories hold that they are desires rather than beliefs. Each of these traditions tries to accommodate or explain away what the_x000D_other tradition handles so easily. One often gets the sense that the defenders of these increasingly complex theories are trying to force a square peg into a round hole. So-called "hybrid theories" try to have the best of both worlds by understanding normative judgments as constituted by both_x000D_belief-like and desire-like states
2.4 Impasse3. Disagreement in Prescription -- 4. Ecumenical Expressivism and Disagreement in Prescription -- Conclusion -- 7: Truth -- 1. Ecumenical Expressivism, Truth-Aptness, and Subjectivism -- 2. The Deflationist Gambit -- 3. The Truth in Ecumenical Expressivism -- 4. Advantages of this Approach -- 5. The Explosion of the Normative? -- 6. What if Soames is Wrong? -- Conclusion -- 8: Rationality -- 1. Rational Capacities -- 2. Rationality as a Success Notion -- 3. Ecumenical Cognitivism Revisited -- 4. Discontinuities Revisited -- Conclusion
Print version record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Norm (Philosophy); Practical judgment; Practical reason; Norme (Philosophie); Jugement pratique; Raison pratique; PHILOSOPHY -- Ethics & Moral Philosophy; PHILOSOPHY -- Social; Norm (Philosophy); Practical judgment; Practical reason